Internalisasi Nilai Keshalihan Sosial dan Toleransi pada Siswa Non Muslim di SDN 5 Cerme Bondowoso - Azisi, Azisi; Mulyono, Mulyono; Hidayatullah, Moh Nur (Prodi PGMI STAI Al-Akbar Surabaya, 2024)
This study aims to explore the internalization process of social piety values and tolerance among non-Muslim students at SDN 5 Cerme Bondowoso. The research employs a qualitative method with a case study approach, involving in-depth interviews, observations, and documentation. The findings indicate that social piety values are internalized through programs such as social service and interfaith interactions, which enhance tolerance, empathy, and student care. Moreover, positive interactions between Muslim and non-Muslim students, particularly during joint celebrations, strengthen mutual respect. The role of teachers is significant in creating an inclusive atmosphere and supporting discussions on diversity differences. Overall, this research finds that a supportive school environment can contribute to the formation of a harmonious and inclusive society. The results provide recommendations for other schools in Indonesia to implement similar programs to support values of tolerance and social piety.